SKEMA AKTAN DAN MODEL FUNGSIONAL PROBLEMATIKA SOSIAL MASYARAKAT MAMUJU TEORI NARATOLOGI A.J.GREIMAS - Nurfadhilah Salahuddin; Rachmat Barung; A.Muh.Ayyub Ht (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
This study aims to understand the representation of social problems in Mamuju society in local online and offline news media through Algirdas Julius Greimas's narratological structural approach. The research focuses on mapping actant schemes and analyzing functional models to uncover role relationships, event flows, and the construction of meaning in news reports. The method used is descriptive qualitative with a narrative analysis design, using data in the form of purposively selected news texts. Data collection was conducted through documentation and literature review, while analysis included identifying narrative units, mapping actants, analyzing functional models, and interpreting social contexts. The results show that the media tends to position certain actors as dominant subjects, while vulnerable groups are affected. The narrative pattern generally moves from the initial situation, through conflict, to a resolution that is not always complete. This study confirms that Greimas's approach is effective in uncovering the structure of meaning and the construction of social reality in news texts.